The Influence of Thai Traditional Philosophical Thought on Contemporary Educational Policies - Somchai Rakpathum; Ananya Silpachai (Al Kautsar: Knowledge Advancements in Teaching Strategies and Research, 2025)
This study explores the foundational role of Thai traditional philosophical thought in shaping the landscape of contemporary educational policies in Thailand. Historically rooted in a synthesis of Theravada Buddhism, Brahmanism, and local animistic beliefs, Thai philosophy emphasizes holistic development, moral integrity, and the "Middle Path." This paper examines how these classical tenets are integrated into modern frameworks, such as the Sufficiency Economy Philosophy (SEP) applied to schooling and the National Education Act. Through a qualitative analysis of policy documents and philosophical texts, the research highlights a unique tension and synergy between Western-style globalization which prioritizes competitive skill sets and traditional values that prioritize "Right View" and communal harmony. The findings suggest that while modern policies strive for technological advancement, Thai traditional philosophy remains a critical anchor for maintaining national identity and fostering ethical citizenship. Ultimately, this research provides insights into how indigenous wisdom can serve as a corrective and complementary force to global educational trends.